Breve reflexión sobre las ideas de civilización, cultura y religión. Pseudoteorías del miedo y bases para el diálogo en la sociedad internacional - Bustos, Rafael (UNISCI Discussion Papers, 2007)
This article is a series of reflections on the changing ideas of civilization, culture and religion. The very idea of civilization was long time used by international jurists as an ideological construct to justify the conquest and enslavement of “barbarian” and “savage” peoples. Only on rare occasions, “civilization” has been analyzed and not merely “used”, following scientific criteria. This is the case of N. Elias who describes a historical process although incomplete of violence contention. From a perspective based on dialogue, I stress the potential for peace and understanding present in some world visions every civilization carries within.